From Liberalization Towards Integration: Have Markups of EU Electricity Firms Changed? - Ziga Zarnic (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
This paper presents an ex-post empirical analysis of the impact of European electricity mar- ket refirms on markups ofirms. The working hypothesis is that further economic integration would bring competition into electricity markets re ected by lower markups of electricityfirms. The results show that refirms have gradually reduced the markups, but the markup premium of incumbentfirms is on average larger than theoretical models would predict under e ective economic integration. Considering regional proximity and heterogeneity ofirms along the supply chain, the results suggest that better market access and cross-border arbitrage disci- plined the markups, but have not led to competitive market outcomes due to prevailing market concentration and insufficient unbundling of transmission and distribution channels.
Keywords: F10; L11; L51; L94; 330; Economic integration; electricity rms; EU; price-cost margins; service market regulation; Energiewirtschaft; Produktivität; EU-Energiepolitik; Deregulierung; EU-Staaten